CULTURAL GUIDELINES FOR COMPANIES OPERATING INTERNATIONALLY: NAVIGATING GLOBAL MARKETS WITH SENSITIVITY AND RESPECT - Sorongon, Chris G.; Yuesti, Anik (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
As businesses increasingly expand into international markets, understanding and respecting cultural differences becomes imperative for success. This research examines the cultural guidelines that companies should adopt to navigate global markets effectively. The study reviews existing literature on cross-cultural management, presents empirical cases demonstrating the impact of cultural sensitivity on business performance, and outlines methods for mitigating cultural misunderstandings. It concludes with recommendations for companies, highlighting the importance of cultural competence in achieving sustainable global operations. The aim of this study is to delve into the significance of cross-cultural integration in international business management. In the context of globalization, cross-cultural integration has become a key factor for businesses to gain a competitive advantage in the international market. A profound understanding and effective utilization of cultural diversity enable businesses to better address challenges in the international market, enhance their competitiveness, and achieve sustainable development. This research will focus on the impact of cross-cultural integration on business strategies, team collaboration, market expansion, etc., aiming to provide management strategies and decision references for businesses and further advance the theory of international business management. Through in-depth research and empirical analysis, this study aims to offer a comprehensive and profound international management perspective, providing crucial guidance and support for businesses to stand resilient in global competition.